Distribution and chromosomal variation in the scincid lizard genus Lygosoma (Reptilia: Squamata) in Thailand - Varanya Aranyavalai; Kanok Lertpanich; Warawut Chulalaksananukul (My University, 2013)
The distribution of the scincid lizard genus Lygosoma in Thailand was studied and recorded on a map. In addition, the studies on chromosomes of Lygosoma bowringii, L. khoratense and L. quadrupes were examined. The karyotype was determined for each individual on the basis of at least 10 well spread cells. L. bowringii and L. khoratense showed the same diploid number of 2N = 32 and identical chromosome morphology. The fundamental number (N.F.) equals 48. The karyotype of L. quadrupes is almost identical to that of L. bowringii, but differs from the latter in having a telocentric pair 9. Thus, the N.F. value equal to 46. No sex chromosome heteromorphisms is evident.
Keywords: Chromosomal and Genetic Variations